Dificuldades na aprendizagem operatória de números inteiros no ensino fundamental - Rocha Neto, Francisco Tavares da (2010)
The present works aimed to identify the causes that make students to have difficulties in the study of integer numbers, verifying accurately the up to what level they manage property that number system, as well to seize the most popular mistakes made by students. In the first part, we offer theoretical bases supported by opinions of authors about the subject. Included in the first part is also a brief history about the evolution of the integer number system, in particular who it appeared, when it started being used, who mathematicians organized the integer numbers system, the origin of the symbols (+) plus and (-) minus. Also in this first part there are comments by authors regarding mathematics education, where they try to justify the low rate of learning in such a discipline. We comment on possible causes of the low performance of students in class and to whom one should blame: Teacher? Student? Educational system? School? For some authors, the success of learning depends a bit on all of these factors, thus teachers, students, educational system and school ought to do their part. Through the didactical strategies suggested, we can understand how the learning process happens and in which situation a student seize the knowledge. In the second part of this work, we perform a research with 100 students from four schools in Fortaleza, making use of two different evaluations. Students are required to ordinate, classify and operate integer numbers. We show the teacher’s methodology, the obstacle faced by students when operating with integer numbers, an analysis of the difficulties in the study of integer numbers, keeping track of the mistakes in order to identify the most often ones in each school and afterwards combat them. Some conclusions, based on the sample data, are delivered at the end of this work, offering also some methodological tools.